MACROMYCETES OF BISHKEK (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article provides an analysis of the species diversity of macromycetes in Bishkek.64 species are registered in the city. The department Ascomycota is represented in 5 species fromthe Rezizales (8%). From the division Basidiomycota, 59 species from 8 orders (92%) were identified. The most numerous is the order Agaricales, represented by 35 species from 23 genera,14 families. The year 2022 was favorable for mushrooms and provoked the development of manytypes of spring-early summer mushrooms.
Keywords: macromycetes, biodiversity, species, order, family.